Dynamics of CO2 assimilation and transpiration rates in plants under changing light conditions - Sumesh K.V; Annamalainathan K; Jacob J (National Seminar on Abiotic Stress Management: Challenges and Opportunities (NSASM 2018), 25-26 October 2018, Tamil Nadu Agriculture University, Coimbatore, India. Souvenir & Abstracts. p. 164.)
CO2 assimilation (A) and transpiration (E) in plants respond to changing light intensities, but E, which depends more on stomatal responses takes more time to act in accordance with the change in light condition than A, resulting in non-coordination between A and E under dynamic light environments. Gas exchange analysis was used to study the temporal responses to varying light intensity and coordination between A and E in Hevea and few other actively photosynthesising species. An uncoupling of A and E was revealed, when there is a sudden variation in light intensity in all the plant species studied. This single leaf data holds true when the fact was analysed in whole plants as well as plantation level, as experimented by xylem sap flow and eddy covariance systems. These studies on fluxes of water and CO2 point to the fact that water efflux out of the leaf remains largely uncoupled from CO2 influx into the leaf as the ambient light conditions change. Early morning and late evening measurements of A and E also indicated the slower response of E to light compared to A, which picks up and falls in accordance with sunrise and sunset, at several magnitudes faster than E under the same condition. We suggest that a rapid stomatl response in accordance to variation in light is essential for preventing continued water loss through transpiration and determining the water use efficiency of crops.
Keywords: CO2 assimilation; Transpiration